Concepções e corporeidades docentes na educação infantil - Romano, Érica Carolina [UNESP] (2015)
Assuming that we are subject bodies and understanding that teachers have great influences on how the students will develop, the goal of this research is to investigate the relation between teachers' conceptions of the body, children and childhood education and their own corporeality. Therefore, aspects regarding the concepts of body guided by different perspectives and authors, authors such as Michel Foucault, Rudolf Laban, Merleau-Ponty and Paulo Freire were approached. The story of the body as socio-historic construction was also briefly resumed, and some considerations related to childhood, child and early childhood education were elaborated, in order to publicize the recognition of this educational stage and, concerning the understanding of their specificities, relate it to the concept of embodiment. To give visibility and analysis to aspects related to the research themes, three educators that work in the stage of childhood education were interviewed through semi-structured interviews, under the foundations of qualitative methodology. The data analysis was constructed in the parallel established between the research questions, the collected data, the inferences made and the theoretical perspectives adopted. Thematic blocks were elaborated from the goals outlined centered on four points. They are: a look upon the conception of child and the purpose of the education destined to them; a look upon the conception of body, a look upon the practices of the childhood educator regarding the place that gives to the body from the understanding about it; a look upon what the concepts and corporeality reveal about the ways of being in the world and in the school. The analyzed data indicate the importance of the teaching reflection, awareness of the historical and social conditioning and the adoption of strategies of action in teaching so that the education professionals effectively take educational function, and based on this understanding, take ...